Analisis Keakraban Pertemanan Mahasiswa Baru dan Pertemanan Mahasiswa Tingkat Atas Pada Mahasiswa Ilmu Komunikasi Universitas Singaperbangsa Karawang (UNSIKA) - Radja Khaharudin Syah; Fitriani; Rosy Fitriyah; Verent Putri K.M; Nurani Masyita (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2024)
This study entitled “Analysis of Friendship Familiarity of Freshmen and Upperclassmen Friendships in Communication Science Students of Singaperbangsa University of Karawang (UNSIKA)” aims to analyze the level of friendship familiarity between freshmen and upperclassmen and analyze the factors that influence these differences. Social Penetration Theory and Phenomenology Theory are used to understand the dynamics of social relationships in an academic environment. The research methods used are case study, phenomenology, and descriptive. The results of this study show that freshmen are more explorative in friendships, while senior students are more selective and focus on relationship quality.